Electricity principles & applications - Fowler, Richard J. (McGraw-Hill, 2013)
This widely-used text prepares students for entry-level jobs in electronics, electrical trades and related fields. Its level and approach are ideal for both electronics and electricity programs looking for a relatively short, applied book covering DC/AC circuits.